Students’ Metacognition and Self-Regulated Learning: An Analysis Through Students’ Work in Solving HOTS Problem - Imas Ismayati; Nani Ratnaningsih; Supratman Supratman (STKIP Singkawang, 2020)
The aims of this study are to analyze and describe the metacognition of students who have high, moderate, and low Self-Regulated Learning (SLR) in solving Higher Order Thinking Skills (HOTS) type problem. The research method that used was qualitative, research subjects were taken from students who can provide information about the results of their work to obtain complete data and stop when there was no information that can be extracted (saturated data), then obtained 6 people consisting of students who have high, medium, low SLR. The Data collection technique used was the think-aloud method. The data analysis technique used in this study was a model from Miles and Huberman. Based on the data analysis, it can be concluded that: the metacognition of students with high SLR used metacognition in the indicators to compose strategies and monitor actions to the maximum while at the evaluation stage they had not been able to mention other alternatives to solve the problem, the metacognition of students with medium SLR used metacognition to the maximum in the indicators of the stage of compiling strategies but at the monitoring actions they had not been able to interpret the results of the answers and at the stage of evaluation they had not been able to mention other alternatives to solve the problem, the metacognition of students with low SLR had not been able to use metacognition to the maximum. Teachers must pay attention to students' self-regulated learning and metacognition in solving HOTS problems.